2023
DOI: 10.1001/jamanetworkopen.2023.5870
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Firearm Injury Intent in Electronic Hospital Records Using Natural Language Processing

Abstract: ImportanceInternational Classification of Diseases–coded hospital discharge data do not accurately reflect whether firearm injuries were caused by assault, unintentional injury, self-harm, legal intervention, or were of undetermined intent. Applying natural language processing (NLP) and machine learning (ML) techniques to electronic health record (EHR) narrative text could be associated with improved accuracy of firearm injury intent data.ObjectiveTo assess the accuracy with which an ML model identified firear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…• When the narrative described an incident as a drive-by shooting or shot by someone else while in a car with no documented/undetermined injury cause, intent was classified as assault. This approach is consistent with federal coding recommendations [14][15][16][17] and prior studies with manual firearm injury intent classifications.…”
Section: Plos Onesupporting
confidence: 75%
See 1 more Smart Citation
“…• When the narrative described an incident as a drive-by shooting or shot by someone else while in a car with no documented/undetermined injury cause, intent was classified as assault. This approach is consistent with federal coding recommendations [14][15][16][17] and prior studies with manual firearm injury intent classifications.…”
Section: Plos Onesupporting
confidence: 75%
“…For example, while some studies estimate unintentional firearm injury to represent 16% or less of all nonfatal firearm injury, approximately 60% of ED firearm injury visits in NC are identified as unintentional based on the ICD-10-CM external mechanism of injury codes [ 3 , 4 ]. Several other studies that have documented these coding intent discrepancies and the potential overclassification of nonfatal firearm injury as unintentional relied on urban, Level I Trauma center data from a small number of hospitals [ 5 , 6 ]. For comparison, we aimed to quantify any coding intent discrepancies using data from a statewide system in a predominantly rural state.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this meta-analysis included 27 studies with 179,109 patients and 9025 images. It consisted of four studies involving 23,707 patients focused on syndromic surveillance, 27,29,33,41 12 studies covering 155,402 patients targeting diseases/events/syndromes recognition, [36][37][38][39][40][42][43][44][45]47,48,53 and 11 studies involving 9025 images concentrating on radiology interpretations. 28,[30][31][32]34,35,46,[49][50][51][52] Detailed descriptions of each study are provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Confusion matrices were unsuccessfully derived from two studies, 39,46 and the other 10 reported varying performance. 31,33,36,[39][40][41]43,[45][46][47][48]53 The sensitivity analysis revealed that the mean sensitivity was 0.82 (95% CI 0.73-0.88), specificity was 0.95 (95% CI 0.92-0.97), PPV was 0.14 (95% CI 0.14-0.14), NPV was 1.00 (95% CI 1.00-1.00), F I G U R E 1 PRISMA flow diagram: using NLP in EM research. NLP, natural language processing.…”
Section: Sensitivity Analysismentioning
confidence: 99%